2017
DOI: 10.1016/s1878-6480(17)30385-3
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection from ischemia/reperfusion injury by exogenous galanin fragment

Abstract: Background and purpose: Galanin is a multifunctional neuropeptide with pleiotropic roles. The present study was designed to evaluate the potential effects of galanin (2-11) (G1) on functional and metabolic abnormalities in response to myocardial ischemia-reperfusion (I/R) injury. Experimental approach: Peptide G1 was synthesized by the 9-fluorenylmethoxycarbonyl (Fmoc)-based solid-phase method. The chemical structure was identified by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The data in the present study showed that miR-221-3p elevated LdH activity in H9c2 cells incubated with H 2 O 2 . LdH is known to be released from cells when the cell membranes are disrupted (19); therefore, in the present study, the increased LdH activity of H9c2 cells represented increased damage to cell membranes. Additionally, in the rat myocardial I/R injury model, the results indicated that miR-221-3p was markedly increased in the area-at-risk and that, following the forced expression of miR-221-3p, the number of myosin + cells and FSLVd% were upregulated and downregulated, respectively.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The data in the present study showed that miR-221-3p elevated LdH activity in H9c2 cells incubated with H 2 O 2 . LdH is known to be released from cells when the cell membranes are disrupted (19); therefore, in the present study, the increased LdH activity of H9c2 cells represented increased damage to cell membranes. Additionally, in the rat myocardial I/R injury model, the results indicated that miR-221-3p was markedly increased in the area-at-risk and that, following the forced expression of miR-221-3p, the number of myosin + cells and FSLVd% were upregulated and downregulated, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…Lactate dehydrogenase (LDH) activity measurement. LdH, an enzyme that catalyzes the conversion between lactate and pyruvic acid, is a diagnostic criterion for MI (19). LdH activity was measured for each group using an LDH detection kit (Beyotime Institute of Biotechnology) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that galanin induces cardioprotective effects against myocardial I/R injury in animals (Pisarenko et al, 2017;Martinelli et al, 2021). Administration of this peptide prevented cardiomyocyte apoptosis and improved metabolic status of the myocardium in vivo (Timotin et al, 2017). The molecular actions of galanin are mediated through three galanin receptors subtypes, GalR1, GalR2 and GalR3 belonging to G protein coupled receptors, and signaling via multiple transduction pathways, including inhibition of cyclic AMP/protein kinase A (GalR1, GalR3) and stimulation of phospholipase C (GalR2) (Howard et al, 1997;Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…We have recently demonstrated that galanin inhibits mitochondrial ROS production and hypertrophy in cardiomyoblasts (Martinelli et al, 2021;Timotin et al, 2017). Therefore, we next examined whether the siRNA-mediated knockdown of GalR2 could affect galanin-mediated effects on cardiomyoblast hypertrophy and ROS accumulation induced by isoproterenol (ISO) treatment.…”
Section: Galanin Orchestrates Cell Hypertrophic and Ros-associated Ce...mentioning
confidence: 99%
See 1 more Smart Citation